Sticktight Flea, Echidnophaga gallinacea - P.G. Koehler; R.M. Pereira; P.E. Kaufman (EDIS)
This document provides an overview of the sticktight flea, Echidnophaga gallinacea, which affects dogs, cats, poultry, and other animals. It describes the flea's biology, behavior, and appearance, noting its small size and lack of combs. The article highlights the health effects of flea infestations, including secondary infections and anemia in young animals. Control measures include manual removal, application of flea products, and environmental treatments to prevent reinfestation. The document emphasizes the importance of proper treatment to avoid further complications and ensure the well-being of affected animals. Publication date: October 1991.